IMPLEMENTASI TANGGUNG JAWAB PELAKU USAHA DALAM PRAKTEK PEMBULATAN PEMBAYARAN SEWA WARUNG INTERNET TERHADAP KONSUMEN DI KOTA PEKANBARU - Dinda Febriani Ramali; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Consumer protection is a term used to describe the legal protectionafforded to consumers in an attempt to satisfy their needs from things that canharm consumers themselves. Consumer protection laws exist to protect consumersthemselves. Consumers must be critical in using that is by prioritizing